Threshold responses of freshwater fish community size spectra to invasive species - Bradley Novak; Brent A. Murry; Jeff S. Wesner; Vojsava Gjoni; Caroline C. Arantes; Erin Shepta; Justin P. F. Pomeranz; James R. Junker; Kathrine Zipfel; Andrew Stump; Levi E. Solomon; Kristopher A. Maxson; et al. (Ecosphere)
Abstract Aquatic invasive species (AIS) threaten biodiversity and ecosystem services around the world, but their management has been hampered by the lack of quantifiable control targets. The introduction of Silver Carp (Hypophthalmichthys molitrix) throughout the mid‐western United States epitomizes both the impacts of AIS and the need for quantitative control targets. Silver Carp are large‐bodied planktivores that compete with native planktivores, which can cause cascading effects throughout the food web. Our study tested the threshold of abundance beyond which Silver Carp alter fish assemblage structure. We used a community size spectra (CSS) approach to evaluate fish community size structure across temporal and spatial gradients of Silver Carp abundances. We hypothesized that Silver Carp would flatten the size spectra slope because they are large‐bodied and feed at a low trophic position. Electrofishing data were obtained for the La Grange Pool of the Illinois River (1994–2021) and for six pools of the Ohio River (2015–2020). Results supported our hypothesis, showing a 98% probability that the relative biomass of Silver Carp is positively related to the CSS slope (resulting in “flattening”). This pattern was strongest in the Illinois River, where Silver Carp made up >30% of fish assemblage biomass in recent years. The pattern was weakest in the Ohio River (78% probability of a positive relationship) where Silver Carp rarely exceeded 20% of total fish biomass. Subsequent changepoint models indicated that a Silver Carp relative biomass of ~24% represents a threshold below which negative food web impacts should be minimized. Our study demonstrates a clear shift in fish community size structure following invasion by Silver Carp and suggests that pre‐invasion CSS slopes may serve as a restoration target. It also illustrates the benefits of CSS to guide Silver Carp and other AIS management.